Castration‐induced changes in the expression profiles and promoter methylation of the GHR gene in Huainan male pigs. (7th December 2016) - Wang, Jing; Chen, Junfeng; Zhang, Jiaqing; Gao, Binwen; Bai, Xianxiao; Lan, Yali; Lin, Ping; Guo, Hongxia; Gao, Yuan; Xing, Baosong
Abstract: Castration plays a regulatory role in growth and carcass traits, particularly in fat deposition, but its molecular mechanisms are still not clear. The present study showed that castration significantly reduced the serum growth hormone and the responses of the growth hormone receptor ( GHR ), insulin‐like growth factor 1 ( IGF‐I ), IGF‐IR and peroxisome proliferator‐activated receptor gamma ( PPARγ ) to castration were similar in different adipose tissues. However, the GHR expression trends were opposite between the liver and the adipose tissues; bisulfite sequencing PCR (BSP) showed that its methylation in these two tissues was different. In particular, the GHR methylation rate in the liver of castrated and intact pigs were 93.33% and 0, respectively, which was consistent with its higher expression level in the intact group. It was predicted that there were potential binding sites for 11 transcription factors in the ninth CpG site (which was methylated and demethylated in subcutaneous adipose tissue of the intact and castrated groups, respectively), including androgen receptor ( AR ), CCAAT/enhancer binding protein‐α ( C/EBPα ) and C/EBPβ, all of which are important factors in lipid metabolism. These results indicate that DNA methylation may participate in castration‐induced fat deposition.